Partial Oxidation of Propylene over as Prepared and Acid Enriched Bi2Mo1-xWxO6 System - Shambhu Sakharam Parab; S.J. Naik; A.V. Salker (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The compounds Bi2Mo1-xWxO6 (x = 0.0, 0.2, and 0.4) were obtained through a Citrate sol-gel process. Thermogravimetric differential thermal analysis (TG-DTA), X-ray diffraction (XRD), Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) techniques were used for characterization. Reitveld refinement of the XRD data confirmed the crystal structure of all the compositions to be orthorhombic, having Pca21 space group. XPS studies indicated the presence of +6 as well as +4 oxidation state for Mo. Surface acid enrichment of all the catalysts was done and monitored by NH3-TPD studies. Partial oxidation of propylene was studied over all the compounds. The W doping was found to increase the catalytic activity. Moreover, as-prepared catalysts and acid enriched catalysts were compared for their catalytic activity wherein, acid-enriched catalysts showed the improved conversion of propylene without hampering the product selectivity profile.